A Comparative Differential Scanning Calorimetry Study of Precipitation Hardenable Copper-Based Alloys with Optimized Strength and High Conductivity - Julia Dölling; Stefanie Felicia Kracun; Ulrich Prahl; Martin Fehlbier; Andreas Zilly (Metals, 2023)
Copper alloys with chromium, hafnium, and scandium combining enhanced strength as well as high electrical and thermal conductivity are analyzed in depth. The aim is to compare the precipitation process during temperature exposure to meet increasing material requirements. This research focuses on alloying elements having a limited, maximum 1 wt.%, and with temperature decreasing solubility in copper. For the simultaneous enhancement of mechanical strength and conductivity, precipitation hardening is the utilized mechanism during the processing of as-casted annealed and quenched specimens and in combination with optional cold-rolling prior to the aging process. Extensive DSC measurements, accompanied by metallographic investigations, and the analysis of hardness and electrical conductivity, lead to a versatile description and comparison of different alloying systems. CuCr0.7 starts to precipitate early and is mainly influenced by the temperature of aging. Provoking the solid solution with cold deformation has a less significant influence on the following precipitation. CuSc0.3 and CuHf0.7 precipitate at higher temperatures and are highly influenced by cold deformation prior to aging. Furthermore, CuHf0.7 and CuSc0.3 show advantages regarding the recrystallization behavior, making them especially applicable for higher operating temperatures. Future research will assess ternary alloy combinations to further scoop the potential.